2007
DOI: 10.1038/sj.npp.1301375
|View full text |Cite
|
Sign up to set email alerts
|

Striatal Adenosine A2A and Cannabinoid CB1 Receptors Form Functional Heteromeric Complexes that Mediate the Motor Effects of Cannabinoids

Abstract: The mechanism of action responsible for the motor depressant effects of cannabinoids, which operate through centrally expressed cannabinoid CB 1 receptors, is still a matter of debate. In the present study, we report that CB 1 and adenosine A 2A receptors form heteromeric complexes in co-transfected HEK-293T cells and rat striatum, where they colocalize in fibrilar structures. In a human neuroblastoma cell line, CB 1 receptor signaling was found to be completely dependent on A 2A receptor activation. According… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
222
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 223 publications
(231 citation statements)
references
References 38 publications
6
222
2
1
Order By: Relevance
“…A 2A -CB 1 and A 2A -D 2 -CB 1 . There is one report on the heteromerization between A 2A and cannabinoid CB 1 receptors (Carriba et al, 2007). It was found that solubilized A 2A and CB 1 receptors coimmunoprecipitate from extracts of rat striatum, where they are colocalized in fibrillar structures.…”
Section: B Adenosine Receptor Heteromersmentioning
confidence: 99%
“…A 2A -CB 1 and A 2A -D 2 -CB 1 . There is one report on the heteromerization between A 2A and cannabinoid CB 1 receptors (Carriba et al, 2007). It was found that solubilized A 2A and CB 1 receptors coimmunoprecipitate from extracts of rat striatum, where they are colocalized in fibrillar structures.…”
Section: B Adenosine Receptor Heteromersmentioning
confidence: 99%
“…A 1 receptor is widely distributed in the brain, including the striatum, while A 2A receptor is mostly concentrated in the striatum [2,3]. It is becoming increasingly obvious that the modulatory role of adenosine in the striatum is related to the ability of A 1 and A 2A receptors to heteromerize with themselves and with other GPCRs, such as dopamine, glutamate, cannabinoid and ATP receptors [4][5][6][7][8][9][10][11][12][13][14]. The present review focuses on the role of one particular adenosine receptor heteromer, the one constituted by the A 2A and the dopamine D 2 receptor, which is already having important implications for the treatment of neuropathologies involving the striatum (see below).…”
Section: Localization Of the A 2a -D 2 Receptor Hetero-mermentioning
confidence: 99%
“…An increasingly accepted rule is that receptor homo-or heterodimers form functional units of GPCR signaling. The ability of opioid [41], A 2A adenosine [42], and D 2 dopamine receptors [43] to heteromerize with CB 1 Rs provides a mechanism to generate differential G-protein coupling at the CB 1 R, thus directly modulating physiological output. Alternatively, eCB signaling at CB 1 Rs can act as either upstream regulator (transactivation, BDNF/TrkB [25]) or downstream signal effector (N-cadherin/FGF-2 at FGF receptor [38,44]) thereby providing differential control of axonal growth and guidance.…”
Section: Expression Dictates Function: Context-dependent Signaling Atmentioning
confidence: 99%